Teori Belajar Multiple Intelligences dan Penerapannya dalam Pendidikan Islam: Analisis Kritis dan Model Integrasi Pedagogis - Yusi Srihartini; Muhamad Aliyudin; Nenden Siti Fatimah Z; R Titin Kustianah; Deden Arif Dinul Hakiki; Muhammad Abdul Muhyi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Background: Howard Gardner's Multiple Intelligences (MI) theory has become an important discourse in modern pedagogy by offering the concept of multiple intelligences. However, its implementation in Islamic Education requires critical study to ensure alignment with Islamic values, particularly in the context of holistic curriculum and learning development. Objective: This research aims to: (1) critically analyze the Multiple Intelligences theory from an Islamic Education perspective; (2) develop an MI pedagogical integration model in Islamic Religious Education learning; and (3) identify implementation challenges along with solution strategies. Method: The research uses a qualitative approach with systematic literature study methods. Data analysis was conducted through thematic content analysis techniques on primary and secondary literature related to MI theory, critical neuroscience, and Islamic education philosophy. Results: The analysis shows that the MI theory has significant pedagogical value for Islamic Education despite limitations in neurobiological validation. The concept of fitrah in Islam can serve as a philosophical foundation for integrating MI with Islamic Education. The developed integration model successfully maps nine types of MI intelligences into Islamic Religious Education competencies with a differentiated learning approach that integrates tawhid and adab values. Conclusion: The MI theory can be applied in Islamic Education as a complementary pedagogical framework, provided it is integrated critically through Islamic value filters. Effective implementation requires adjustment of learning strategies, development of holistic assessment systems, and continuous teacher capacity improvement.